POPULASI DAN TINGKAT SERANGAN HAMA KUTU PUTIH PADA UBI KAYU (Manihot esculenta Crantz) PADA BEBERAPA LOKASI PENANAMAN DI LAMPUNG - Sidarlin Sidarlin; I Gede Swibawa; Agus Muhammad Hariri; FX Susilo (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2020)
The research aimed at studying the level of attack and population of mealybug cassava in multiple cassava planting locations in Lampung Province takes place from September 2017 to January 2018. Sampling was carried out in several cassava planting locations in five villages in five sub-districts in South Lampung, Central Lampung, and East Lampung. Attack crop samples were ten plants that were systematically chosen, each at five sample points located on four diagonal lines and one at the midpoint of each field. One plant at each sample point was selected for observation of the mealybug population. The laboratory process is carried out at the Plant Pests Laboratory, Plant Protection Department, Faculty of Agriculture, University of Lampung. The results showed that mealybug were found in all locations of observation with a low population density of 0.68-3.26 individuals. per 3 leaves. Location of cassava planting does not affect the population of mealybug but this location affects crop damage which ranges from 47 - 59%. Damage to plants in South Lampung is lower than damage to plants in East Lampung and Tanjung Bintang.